Analisis Customer Engagement, Handling Complaint dan Customer Experience dalam Membangun Customer Loyalty di Restoran Kanvill Dau - Nabila, Fitria Sane; Nurhajati, Nurhajati; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the impact of customer engagement, handling complaints, and customer experience on customer loyalty at Kanvill Dau Restaurant. These factors were selected due to their potential in enhancing customer loyalty to the restaurant. The research employs a quantitative approach with a survey method. Data were collected through questionnaires distributed to customers who had visited Kanvill Dau Restaurant, with a total sample of 108 respondents. Multiple linear regression analysis was used to examine the relationship between the independent and dependent variables. The results indicate that customer engagement does not have a significant impact on customer loyalty, whereas handling complaints and customer experience have a significant positive effect on customer loyalty. This suggests that while customer interaction with the brand does not directly influence loyalty, effective complaint handling and a satisfying customer experience can enhance customer loyalty. This study contributes to the literature on service management, particularly in understanding the factors that influence customer loyalty in the restaurant industry. The practical implication of this research is the importance for restaurants to focus on improving customer experience and complaint handling to strengthen customer loyalty. Keywords: Customer Engagement, Handling Complaint, Customer Experience, Customer Loyalty, Restaurant